Indikator Ketenagakerjaan terhadap Kemiskinan di Indonesia - Asri, Yualita Surya; Wijayanti, Sukma Kurnia; Vianey, Arsdhewani Maria; Kartiasih, Fitri (Jurnal Ekonomi : Journal of Economic, 2023)
This study aims to determine the situation of workers in Indonesia and analyze the factors that cause poverty in terms of employment in an effort to eradicate poverty in Indonesia. The method used is panel regression data covering 34 provinces in Indonesia in 2011–2022. The research results show that the COVID-19 pandemic has had a positive impact on poverty levels in Indonesia, as shown by the increase in the percentage of poor people (P0) during the COVID-19 pandemic period. There has been a massive reduction in the workforce due to the COVID-19 pandemic, as shown by the number of worker and the Labor Force Participation Rate, which has decreased, as well as the Open Unemployment Rate (TPT), which has increased. The Provincial Minimum Wage and the number of worker have significantly reduced poverty in Indonesia.